Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2018)
A dataset containing 1856425 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Procellariiformes" ] } The dataset includes 1856425 records from 492 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002789-181108115102211/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences